The antecedents and consequences of digital competence: How to support the performance of organizations - Farah, Indina; Suseno, Bambang Dwi; Suadma, Udin (Jurnal Ekonomi Modernisasi, 2023)
This study investigates the role of digital competence as a mediator of the relationship between self-efficacy and self-esteem to improve the organizational performance. Performance is the focus that we want to examine and find solutions to, considering that only three of the nine Civil Service Police Units have received very good SAKIP. Four good categories and one insufficient category. This study uses a quantitative approach through structural equation modeling partial least squares (SEM-PLS) analysis. The population of this research is structural officials of echelon 2, 3, 4 and functional officials, they obtained a sample of 107 people. Exogenous variables in this study are self-efficacy, self-esteem, digital competence, and organizational performance as endogenous variable. The results of testing four accepted hypotheses and one rejected hypothesis. Digital competence has a mediating role in the influence of self-efficacy and self-esteem on organizational performance The research results have not succeeded in showing that self-efficacy has an effect on improving the organizational performance.